2021
DOI: 10.1177/13524585211012227
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of cladribine in MS: Real-world experience from two tertiary centres

Abstract: Background: Oral cladribine has been approved for the treatment of relapsing multiple sclerosis (MS) yet real-world evidence regarding its effectiveness and safety remains scarce. Objective: To evaluate efficacy and safety outcomes of MS patients following induction of cladribine. Methods: We evaluated our prospective cohort of cladribine-treated MS patients from two tertiary centres in Germany. Relapses, disability worsening and occurrence of new or enlarging T2-hyperintense magnetic resonance imaging (MRI) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 22 publications
3
57
1
1
Order By: Relevance
“…Despite analyzing a cohort substantially comparable in terms of sample size and demographic- and disease-related features to the one recruited from Germany tertiary centers [ 12 ], we did not identify any prior exposure to specific DMTs as risk factor for suboptimal response to cladribine.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite analyzing a cohort substantially comparable in terms of sample size and demographic- and disease-related features to the one recruited from Germany tertiary centers [ 12 ], we did not identify any prior exposure to specific DMTs as risk factor for suboptimal response to cladribine.…”
Section: Discussionmentioning
confidence: 96%
“…More recently, additional analyses suggested a better response in patients with high disease activity in the year prior to cladribine start [ 9 ], regardless of their pre-enrollment treatment status (naïve or previously treated) [ 10 ]. Data from real-world studies, including less disabled patients with RRMS with shorter disease duration and a larger variety of previous treatments compared with the RCTs, have suggested suboptimal disease control in cladribine-treated patients switching from natalizumab [ 11 ], and a higher risk of severe lymphopenia and subsequent herpes virus infections in patients previously treated with dimethyl fumarate [ 12 ]. As the MS therapeutic portfolio continues to expand, the identification and confirmation of potential risk factors of suboptimal response to specific disease-modifying therapies (DMTs) is of fundamental value.…”
Section: Introductionmentioning
confidence: 99%
“…However, regarding confirmed disease progression for 6 months, NEDA, and overall adverse event risk, oral cladribine did not differ significantly from most alternative DMDs ( 54 ). A recent study on 270 MS patients from Germany, reported that patients switching from natalizumab to cladribine tablets were prone to re-emerging disease activity ( 55 ). Similarly, recent evidence from patients switching from natalizumab to other DMDs shows that cladribine has a higher risk for relapses and MRI activity than ocrelizumab, but similar to rituximab ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…As older patients with MS in the real world are likely to have received prior DMTs, it is unclear how immunosenescence and prior DMT use might impact the effect of cladribine tablets in these patients; this is a subject that requires further research. Recently published realworld studies of cladribine tablets patients (mostly non-elderly) who switched from another DMT showed that cladribine's effect on lymphocyte changes and clinical and magnetic resonance imaging outcomes were broadly similar in those who were previously untreated compared with those previously treated with DMF, fingolimod, beta-interferons, glatiramer acetate, or teriflunomide (29,30). Adverse events were also shown to be similar in a small group of patients treated with cladribine, ocrelizumab or rituximab after immediate prior natalizumab use.…”
Section: Discussionmentioning
confidence: 99%